2016
DOI: 10.3832/ifor1441-008
|View full text |Cite
|
Sign up to set email alerts
|

Public attitudes towards the use of transgenic forest trees: a cross-country pilot survey

Abstract: (18)Information on public attitudes towards the use of transgenic trees in forest plantations is important in the decision-making process and policy implementation for safe tree development, particularly at the EU level. In Europe, the use of transgenic forest trees is very limited and therefore such information is completely lacking. To address this issue within the FP0905 European COST Action on the Biosafety of Transgenic Forest Trees a pioneer cross-country pilot survey on public attitudes towards the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…In a sample of students in multiple countries (mostly European), Kazana et al . () found generally positive attitudes toward using GE of trees in plantations, but not in wild natural forests. In a sample of the public in the USA, Needham et al .…”
Section: Impacts Of Reproductive Modificationmentioning
confidence: 92%
See 4 more Smart Citations
“…In a sample of students in multiple countries (mostly European), Kazana et al . () found generally positive attitudes toward using GE of trees in plantations, but not in wild natural forests. In a sample of the public in the USA, Needham et al .…”
Section: Impacts Of Reproductive Modificationmentioning
confidence: 92%
“…Compared to agriculture, attitudes toward GE in trees and forests are less understood and there are only a few studies of attitudes about reproductive modification in forest trees (Strauss et al, 2009). In a sample of students in multiple countries (mostly European), Kazana et al (2015) found generally positive attitudes toward using GE of trees in plantations, but not in wild natural forests. In a sample of the public in the USA, Needham et al (2015) found that attitudes were less favorable toward using GE in wild forests compared to other forestry techniques (e.g.…”
Section: Social Dimensionsmentioning
confidence: 93%
See 3 more Smart Citations